2012
DOI: 10.1080/15710882.2011.637113
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of horizons: Co-designing with Cambodian children who have prosthetic legs, using generative design tools

Abstract: This paper presents a field study exploring the challenges and implications of applying a participatory design process through the use of generative design tools with children using prosthetic legs in rural Cambodia in order to facilitate their involvement in the design process. First, it reviews the main research paradigms in which user research is conducted, including positivism, critical theory and interpretivism, and compares the paradigms in terms of the motives they carry for involving users in the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…The first participant group was children (n:15), referring to individuals under 15 years old. Inside this group, there were studies working with children with autism [31,58,64], children at risk of marginalization [2,32], and children that require prosthetics legs [38,39]. The rest of these studies referred to their participants as children [6,26,27,40,46,55,78,83].…”
Section: Involved Participantsmentioning
confidence: 99%
“…The first participant group was children (n:15), referring to individuals under 15 years old. Inside this group, there were studies working with children with autism [31,58,64], children at risk of marginalization [2,32], and children that require prosthetics legs [38,39]. The rest of these studies referred to their participants as children [6,26,27,40,46,55,78,83].…”
Section: Involved Participantsmentioning
confidence: 99%
“…Some social robotic groups modified the UTAUT to include core measures that would fit their product, and BMI is seen to be in need of a more tailored evaluation [141][142][143]. We submit that human-centered designs [172][173][174] (or user centered design [142]) and a participatory design process [175,176], which involves co-designing with generative design tools [177], is one possible avenue that could be utilized more by researchers and engineers. The participatory design could start with a modified UTAUT with open-ended questions covering design, needs, motivation and social factor consideration.…”
Section: Modified Technology Acceptance Modelsmentioning
confidence: 99%
“…Greenhalgh et al (2016) demonstrated the potential of co-creative research as an approach that can have a real impact in society because the research can adopt to local cultures. In orthopaedic engineering of prosthetics for children in the Cambodian countryside, the need for co-design emerged (Hussain & Sanders, 2012), and a fusion of horizons of understanding was aimed for (Gadamer, 2004).…”
Section: Introductionmentioning
confidence: 99%